“Internationalization” as a resource of human capital development: preliminary results of a proposed model - Mhd. Sarif, Suhaimi (2010)
Internationalization is a potential sustainable Muslim resource for human capital development. The word “internationalizaton” impresses everyone irrespective of one’s personal or institution’s efforts to align with the idealized internationalization or a few defined by referent organizations. The paper aims to (a) trace the origin of the word and concept of “internationalization” within available literature in English, (b) reconcile between the literature definitions with the usage of the word and concept among selected international organizations, especialy Muslim-controlled and Islamic oriented tertiary institutions, and (c) suggest whether the hybrid concept of internationalization match strategically with the spirit of Kalima Shahada, the very foundation of Islamic belief, which embraces the entire mankind. The proposed study is believed to be significant because it attempts to ascertain the degree of consonance or otherwise that might exist between the two concepts – internationalization and the spirit of Kalima Shahada, and project a pattern of responses that might be expected from the Muslim organizations and nations towards the concept of “internationalization” in its various forms. The study used textual analysis to develop a model of internationalization which reflects the kalima shahadah. It then tested the proposed model with the independant raters (n=78). The authors consolidated the components in the literature and practice to propose five connections that reflect the status of being “international”. However, the results confirm only three out of five proposed connections.